Efecto analgésico del aceite cannabidiol (CBD) en el post operatorio de ooforosalpingohisterectomía en cannis familiaris - Achi Santibañez, Annerys Mercedes (2021)
This research was developed in the "DR MILLER" Veterinary Clinic, the analgesic effect of cannabidiol oil (CBD) of 300 mg orally in the postoperative period of oophorosalpingohysterectomy in canis familiaris was evaluated at a dose of 2 mg / kg every 6 hours in 20 female dogs, for comparison effect, 10% ketoprofen was used intramuscularly at a dose of 1 mg / kg every 24 hours, the t-Student technique was used and in both groups pain was measured by (Modified Glasgow Scale) every two hours for three days, CBD oil was superior in pain control, highly significant differences (p <0.001) were found at eight hours with 1.95 / 24 (points on the Modified Glasgow Scale), from 54 0.10 / 24 hours, a value that remained stable up to 72 hours, compared to ketoprofen at two hours a value of 4.80 / 24 was obtained and at 66 hours 2.75 / 24, a value that rose until one hour 72 to 3.10 / 24. The physiological variables of frequencies (heart and respiratory) rectal temperature were measured every 12 hours, they remained within the normal range in both groups, CBD oil had an average cost of the product of $15.99 (dollars), ketoprofen resulted at an average product cost of $ 0.12 (dollars). It is concluded that CBD oil proved to be effective in controlling the intensity of pain and was superior to ketoprofen, no side effects were observed, CBD gave a state of well-being in its analgesic effect.